Skugga: the wayang kulit kit / Nurul Hidayah Zainuddin - Zainuddin, Nurul Hidayah (Faculty of Art and Design, 2020)
Nowadays, our new generation have not been aware and even show interest in our traditional culture. Because of that, the idea of making Wayang Kulit popular again came to make sure it would still be relevant today.